New Words in Serbian Public Discourse as a Consequence of the COVID-19 Pandemic - Nikolić, Marina; Slijepčević Bjelivuk, Svetlana; Novokmet, Slobodan (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
The aim of this work is to present the lexical changes in the Serbian language caused by the COVID-19 pandemic. The paper analyses new words that appeared in the Serbian language which very quickly expanded the domain of their use from specific medical terminology and became part of everyday spoken Serbian language, including new words motivated by them. Types of neologisms emergence are presented (borrowing from the English language, changing or developing new meanings of the existing words, exploiting the derivative potential of the Serbian language, etc.), as well as their stylistic, orthographic, and pragmatic features. After a detailed analysis, we included a dictionary of neologisms followed by the indispensable comments.